Brain abscess and periodontal pathogens (Fusobacterium Nucleatum). Report of a case - Debora Franceschi; Valentina Giuliani; Veronica Giuntini; Giovanpaolo Pini Prato (Clinical Case Reports, 2020)
Abstract Patients who develop brain abscesses must be evaluated through a complete set of diagnostic tests including a microbiological and clinical periodontal assessment. A genetic comparison of the pathogens from intracranial/extracranial sites is necessary.